443 INTRAUTERINE GROWTH RETARDATION AFFECTS POSTNATAL RIBONUCLEIC ACID LEVELS OF PROTEINS INVOLVED IN RETINOIC ACID SIGNALING AND METABOLISM. Issue 1 (1st January 2007) - Burshears, B.; Hale, M.; Yu, X.; Callaway, C.; Langen, R.; Caprau, D.; O'Grady, S.; McKnight, R.; Lane, R.
Abstract : Introduction: Intrauterine growth retardation (IUGR) affects postnatal hepatic gene expression. Many of these changes are secondary to epigenetic modifications of chromatin, which are often gender specific. The gender-specific effects of IUGR upon chromatin structure widens from day of life (DOL) 0 through DOL 21. The signaling mechanism responsible for the progressive difference between the genders is unknown. Preliminary data from differential display RT-PCR experiments suggest that IUGR affects mRNA levels of protein involved in retinoic acid metabolism. These findings are intriguing because retinoic acid and its receptors are known to alter chromatin structure in multiple cell culture systems. Hypothesis: We hypothesized that IUGR would alter mRNA levels of the following genes involved in retinoic acid signaling and metabolism: RARα (receptor), RARβ (receptor), RARγ (receptor), aldh1a1 (synthesis), aldh1a2 (synthesis), CYP26a1 (degradation), and Rbp1 (transport). Methods: Induction of IUGR was done through bilateral uterine artery ligation of the pregnant rat at day 19 of gestation with delivery by cesarean section on day 21.5 (term) of gestation. Using liver tissue from day 0 and day 21 rat pups, mRNA was isolated, cDNA synthesized, and RT-PCR used to analyze the genes listed above. Results: IUGR significantly decreased RARγ expression in DOL21 female livers ( p < .05), without significantly affecting RARγ levels in the DOL21 male livers. In contrast, IUGR significantly decreased CYP26a1 levels in the DOL21 male livers ( p < .05), without significantly affecting CYP26a1 levels in the DOL21 female livers. At DOL 0, mRNA levels of Rbp1 were significantly decreased by IUGR in both genders. Conclusion: IUGR induced by uteroplacental insufficiency increases mRNA levels of RAR γ in female IUGR liver and decreases mRNA levels of CYP26a1 in male IUGR livers. These gender-specific differences are intriguing, considering that they parallel the gender-specific differences in chromatin structure and histone modifications previously described. Furthermore, the decrease in male CYP26a1 levels suggests that the male IUGR rat is vitamin A deficient, despite 3 weeks of ad libitum feeding. We speculate that the gender-specific differences in RA signaling and metabolism may play a role in the progressive gender differences observed in the IUGR rat.